1975
DOI: 10.1002/jobm.3630150808
|View full text |Cite
|
Sign up to set email alerts
|

Virusartige Partikeln in Hefeprotoplasten. I. Elektronenmikroskopischer Nachweis

Abstract: In ultrathin sections and negatively stained isolates from protoplasts of a strain of Saccharomyces cerevisiae showing abnormal morphology and degeneration phenomena the presence of virus-like particles within the cells could be demonstrated. The isometric particles have diameters of about 50 nm, the electron dense centre is surrounded by distinct envelope. Protoplastic containing up to 30,000 particles could be found. It could be demonstrated that there exists a correlation between the amount of particles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This puts a lower limit on the number of Sc V particles per cell. In at least one strain of yeast, there may be as many as 30,000 ScV particles per cell, as judged by electron micros copy of thin sections (94). This last study also clearly locates the ScV particles in the cytoplasm, outside cytoplasmic organelles.…”
Section: Physical Properties Of Scv Particlesmentioning
confidence: 94%
See 1 more Smart Citation
“…This puts a lower limit on the number of Sc V particles per cell. In at least one strain of yeast, there may be as many as 30,000 ScV particles per cell, as judged by electron micros copy of thin sections (94). This last study also clearly locates the ScV particles in the cytoplasm, outside cytoplasmic organelles.…”
Section: Physical Properties Of Scv Particlesmentioning
confidence: 94%
“…Electron microscopy of ScV-L by a number of investigators (2,18,39,44) has demonstrated particles roughly 40 nm across, some of which have a crudely hexagonal outline ( Figure 1) [e.g. see (94)]. Such an outline would be consistent with an icosohedral particle.…”
Section: Physical Properties Of Scv Particlesmentioning
confidence: 95%
“…During replication of these colonies proportion of blue ones rapidly decreased concomitantly with the amount of VLP in the cells. WEBER and LINDNER 1975). Electron microscopy of the cells also shows the absence of lytic infection, as the particles were only present in few cells.…”
Section: Resultsmentioning
confidence: 94%
“…While plating the VLP-containing yeast cells, plaques were not found. Neither have plaques been found before (LINDECREN et al 1962, LHOAS 1972, VOLKOFF and WALTERS 1970, WEBER and LINDNER 1975. Electron microscopy of the cells also shows the absence of lytic infection, as the particles were only present in few cells.…”
Section: Virus-like Particles In Yeast 207mentioning
confidence: 85%